TEKNOLOGI PENGOLAHAN PATI GARUT DAN DIVERSIFIKASI PRODUK OLAHANNYA DALAM RANGKA PENINGKATAN KETAHANAN PANGAN - Ratnaningsih, Nani; Nugraheni, Mutiara; Handayani, Titin Hera Widi; Chayati, Ichda (Universitas Negeri Yogyakarta, 2010)
The objectives of community development activity are: 1) give alternative of processing technology of arrowroot for group of farmer KSM Mekar Sari di Desa Gegunung, Kel. Sendangsari, Kec. Pengasih, Kulon Progo, Yogyakarta, so that can yield arrowroot starch that fulfills standard quality with appropriate packaging and labeling; 2) know extraction technology efficiency of arrowroot starch with mechanically hydraulic press; 3) give alternative of food product to consumer in the form of arrowroot starch-based cookies that high nutrition and fulfills standard quality; and 4) give an opportunity for home industry with exploiting of arrowroot so can be empowered and increases public prosperity, especially farmer arrowroot. The community development activity was done from July up to November 2009 and divided to become some phases, that is preparation, implementation and evaluation. At preparation phase was done by designing of extraction arrowroot starch machine, making of hydraulic press machine for arrowroot starch extraction, making of arrowroot starch-based cookies, design of packaging and labeling, making of training matter and evaluation sheet. Implementation phase was done with discourse method, discussion, demonstration, practice of processing technology of arrowroot starch with hydraulic press machine, and practice of making of arrowroot starch-based cookies for general and diabetic consumer. Discourse matter contains about arrowroot characteristics and damage cause, processing technology of arrowroot, packaging and labeling, sanitary and hygiene, food safety, and economic analysis in the form of determination of production cost, selling price and BEP. Evaluation phase covered evaluation of input, process, product, and satisfaction of activity participant. Based on result and discussion can concluded that: 1) Community development activity have been done on 1 and 15 November 2009 followed by 21 members of group of farmer KSM Mekar Sari; 2) Extraction technology of arrowroot starch with hydraulic press machine can yield arrowroot starch closing standard quality of arrowroot starch according to SNI with appropriate packaging and labeling; 3) Extraction technology of arrowroot starch with hydraulic press machine more efficiently is compared to separation technique applied before all; 4) Alternative of food product in the form of arrowroot starch-bases cookies to general and diabetic consumer that high nutrition and fulfills standard quality; and 5) Processing technology and diversification of arrowroot starch product can open an opportunity for home industry that can be powered and increases resilience of food on local food material-based